Mapping molecular diversity of indigenous goat genetic resources of Asia - Periasamy, Kathiravan (2017)
The world goat population is approximately 1.0 billion with more than half of them present in Asia. The Joint FAO/IAEA Division of Nuclear Techniques in Food and Agriculture initiated a programme to characterize goat genetic resources of Asia. Nine Asian countries viz. Bangladesh, China, Indonesia, Iran, Pakistan, Sri Lanka, Vietnam, Myanmar and India were supported to conduct breed surveys, evaluate production environments and assess phenotypic and genetic characteristics of indigenous breeds/populations. This paper reports genetic diversity of 57 goat breeds of Asia located in nine countries and genetic relationship/population structure of 43 breeds located in seven countries. The level of genetic variability among goat breeds/populations across Asia was consistent with the history of domestication, variability being higher near the center of domestication and a decreasing gradient while moving away from this center. Positive directional selection was observed at one or a few microsatellite loci in goat populations of at least four Asian countries including Sri Lanka, India, Iran and Myanmar. Genetic differentiation among goat breeds/populations within different countries varied from 1.9% (Myanmar goats) to 12.6% (Indonesian goats) with a global FST of 12.7%. Genetic differentiation among local goats within countries was limited, an indication of high gene flow across breeds/populations. The microsatellite based phylogeny showed two major clades: the Chinese goats clustered distinctly while the goat breeds from other countries clustered separately in a single clade. Weak genetic structure was observed in Bangladeshi, Sri Lankan and Myanmar goats, moderately strong genetic structure was observed in Pakistani goats while strong genetic structure was observed in Indonesian, Iranian, Vietnamese and Chinese goats. Model based cluster analysis of metadata broadly grouped Asian goats into two major geographical clusters (Chinese and West Asian) which can be partitioned further into four groups: Chinese, West Asian, South East Asian and South Asian. The results from this study clearly established the genetic distinctness of Chinese goats from other major Asian goat breeds.